2018
DOI: 10.1371/journal.pone.0196089
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of open comments to understanding the results from the Hospital Survey on Patient Safety Culture (HSOPS): A qualitative study

Abstract: IntroductionTo develop high-quality and safe healthcare, a good safety culture is an important feature of healthcare-providing structures. The objective of this study was to analyze the qualitative data of the comments section of a Hospital Survey on Patient Safety (HSOPS) questionnaire to clarify the answers given to the closed questions.MethodUsing the original data from a cross-sectional survey of 5,064 employees at a single university hospital in France, we conducted a qualitative study by analyzing the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
2
15
0
4
Order By: Relevance
“…Other factors that contributed to the underreporting of errors could be the limited resources and time that put staff under pressure to focus on the main tasks. This was consistent with the outcomes from a similar French qualitative study 40. In this regard, shortage of staff was noticed among all healthcare specialties and eventually increased HCPs' workload resulting in a stressful working environment.…”
Section: Discussionsupporting
confidence: 89%
“…Other factors that contributed to the underreporting of errors could be the limited resources and time that put staff under pressure to focus on the main tasks. This was consistent with the outcomes from a similar French qualitative study 40. In this regard, shortage of staff was noticed among all healthcare specialties and eventually increased HCPs' workload resulting in a stressful working environment.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding of a perception of insufficient support for patient safety from managers does not seem to have changed since earlier quantitative studies carried out in France [7,21,22]. Our results confirm those from a recent mixed-method study conducted in France that shown an association between, on the one hand, the patient safety culture dimensions scores, and on the other hand, the qualitative perception of SC by caregivers [35].…”
Section: Discussionsupporting
confidence: 86%
“…32,33 For instance, Boussat et al. 36 found staffing to be the most frequently reported failed patient safety culture dimension. This suggests that most of the respondents felt that staff allocation was not adequate to handle patient safety-related workload.…”
Section: Discussionmentioning
confidence: 99%